Development and validation of new economic HPLC method for the analysis of gliclazide in tablet dosage form - Helal Uddin, A.B.M.; Alaama, Mohammed; Mohamad, Huda Jamilah; Amiruddin, Noor Syafawati; Abbas, Syed Atif (2014)
New sensitive and highly economic analytical method for the analysis of gliclazide in tablet dosage form was developed and validated using UHPLC column and HPLC instrument. Standards and samples were prepared by dissolving gliclazide standard or gliclazide tablets in small amount of methanol sonicate for 5 min then top up using mobile phase. Samples were analysed using Agilent 1200 Series RP-HPLC equipped with quaternary pump and auto injector. Samples were injected to C18 HSS water column (2.1X100 mm, 2.5µm) and the mobile phase consisted of triethylamine buffer (pH=3 adjusted using phosphoric acid) and acetonitrile in the ratio 50:50 v/. The flow rate was 0.4 ml/min and UV detector was used for the detection and the wavelength was 229 nm. The method was validated according to ICH guidelines. The retention time for gliclazide peak was 3.437±0.41 min with the total run time of 6 min with total solvent consumption of 2.4 ml per run. The method was found linear over the range 0.1-40 µg/ml with correlation coefficient R2 = 0.999. The recovery was 98.09-100.19 %, and the method showed high precision and repeatability. All validated parameters were in the acceptable range of ICH requirements. In conclusion new rapid sensitive and highly economic method was developed and validated for the analysis of gliclazide in tablet dosage form.